Survival Strategi Pemerintah Daerah dalam Mengatasi Krisis Bahan Pangan di Kota Metro - Safitri, Khansa Kamilia; Firmansyah, Firmansyah; mustaghfiroh, Siti (Wajah Hukum, 2025)
The food crisis remains a significant issue up to the present time. Even though the Government has make an effort to overcoming it through numerous strategies and policies, challenges serving as land conversion, climate change and a decrease of food production remains the primary factors that cause the crisis. This research intended to provide a comprehensive overview of the strategies and regulations executed by the government in handling the food crisis in Metro City throughout 2024. The primary focus of this research is to analyze food security strategies evolved by the Government moreover appraise their effectiveness in optimally responding to the challenges of the crisis. Using a qualitative approach, this research examines various government policies and programs through data obtained from interviews and document analysis. The findings emphasize the significance of well-designed strategies aimed at enhancing local food resilience. The research particularly focuses on the 4K Program (Price Affordability, Supply Availability, Distribution Flow, and Effective Communication), which has proven effective in increasing food availability in Metro City. Nonetheless, challenges remain in terms of price affordability, which warrants further attention. In conclusion, while the 4K Program demonstrates considerable potential in addressing the food crisis in Metro, ongoing evaluation and periodic improvements are essential to ensure the program's long-term sustainability and effectiveness.